Large Bowel Obstruction: Etiologies, Diagnosis, and Management - Chen, Kevin A.; Kapadia, Muneera R. (Clinics in Colon and Rectal Surgery, 2023)
Large bowel obstructions (LBOs) often require urgent surgical intervention. Diagnosis relies on astute history and physical examination, as well as imaging with computed tomography (CT) scan for stable patients. Because of the high mortality associated with colonic perforation in patients with LBOs, decisive surgical decision-making is needed for optimal outcomes. This review seeks to provide an overview of the etiologies of LBO, diagnosis, and general management principles, as well as specific management for the most common etiologies, including colorectal cancer and strictures.
Keywords: large bowel obstruction; colorectal cancer; colonic stent